2011
DOI: 10.1007/s00213-011-2299-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine administration to pregnant rats increases anxiety-related behavior in the offspring

Abstract: Prenatal fluoxetine exposure in rats leads to detrimental behavioral outcomes in later life, which may partly be due to altered 5-HT(1A) receptor signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
154
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(182 citation statements)
references
References 72 publications
24
154
3
1
Order By: Relevance
“…During early life, serotonergic neurons are among the earliest to be generated, and 5-HT has an important role in different processes pivotal for neuronal growth and maturation (Gaspar et al, 2003). Indeed, blockade of SERT during fetal life of rats can lead to negative outcomes on brain function and behavior, including behavioral despair and anxiety-like behavior (Lisboa et al, 2007;Olivier et al, 2011). Moreover, pharmacological blockade of SERT during early post-natal life (PND 4-21) results in increased immobility time in the Figure 3 Chronic duloxetine treatment modulates the levels of neuronal PAS domain protein 4 (Npas4) and aryl hydrocarbon receptor nuclear translocator 2 (Arnt2) gene expression in serotonin transporter (SERT) À/À rats.…”
Section: Discussionmentioning
confidence: 99%
“…During early life, serotonergic neurons are among the earliest to be generated, and 5-HT has an important role in different processes pivotal for neuronal growth and maturation (Gaspar et al, 2003). Indeed, blockade of SERT during fetal life of rats can lead to negative outcomes on brain function and behavior, including behavioral despair and anxiety-like behavior (Lisboa et al, 2007;Olivier et al, 2011). Moreover, pharmacological blockade of SERT during early post-natal life (PND 4-21) results in increased immobility time in the Figure 3 Chronic duloxetine treatment modulates the levels of neuronal PAS domain protein 4 (Npas4) and aryl hydrocarbon receptor nuclear translocator 2 (Arnt2) gene expression in serotonin transporter (SERT) À/À rats.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, two studies found that perinatal SSRIs increased weight at the juvenile stage [84] and adulthood [52], while other studies have failed to find a difference in weight in offspring at pre-weaning [86], at adulthood [84], from pre-weaning into the juvenile stage [13,18,54,56], and from pre-weaning into adulthood [16,52,59,88]. In terms of other types of animal studies, gestational SSRIs in sheep reduced weight of lambs at P2 and P3, but with no difference at P5 [60].…”
Section: Animal Studiesmentioning
confidence: 95%
“…Studies have found that SSRIs during gestation reduced weight at pre-weaning [43,45,46,84], at pre-weaning into the juvenile stage [44,58], at the juvenile stage [85], or at adulthood [48,86].…”
Section: Animal Studiesmentioning
confidence: 99%
“…Following perinatal exposure to Flx, changes observed in adult mice and rats are not always disadvantageous. Flx-exposed rats sometimes perform better than controls, demonstrating better coordination and balance, superior emotional and spatial memory in adolescence [17], and better emotional memory in adulthood [18]. Other findings include decreased anxiety [19], reduced impulsivity [20], and less depressive behaviour [19,20,21] in adult mice.…”
Section: Introductionmentioning
confidence: 99%